Post occupancy evaluation of students’ hostel accommodation in Federal University of Technology, Minna - Olagunju, R.E.; Zubairu, S.N. (Penerbit Universiti Kebangsaan Malaysia, 2016)
The rate of increase in the number of young people seeking admission into universities or other higher institutions of learning and diversity of their needs, makes the issue of students housing a particular problem. Today housing the students is one of the major problems facing most of Nigeria’s higher institutions of learning. This paper provides the results of post occupancy evaluation of students’ hostel accommodation in Federal University of Technology, Minna. The main objectives of this study were to evaluate the state and conditions of the hostel accommodation whilst ascertaining the users’ perception of the buildings with a view to providing practical recommendations for improved comfort. To achieve the desired objectives, data were obtained through primary and secondary sources. This comprised the use of structured questionnaires and observation schedule. A total of 120 Questionnaires were distributed while there was one observation schedule per hostel block. The results indicated that more beds were placed in the rooms than they were designed for, water supply was inadequate and maintenance of the hostels needed to be improved on. It is recommended that maintenance of the hostels should be out-sourced and hostel managers should control room occupancy to prevent overcrowding.